Visual merchandising and customers’ impulse buying behavior: a case of a fashion specialty store / Hadijah Iberahim ... [et al.] - Iberahim, Hadijah; Zulkurnain, Nur Amira Zureena; Raja Ainal Shah, Raja Nazian Adila; Rosli, Siti Quraisyiah (Universiti Teknologi MARA Cawangan Sarawak, 2019)
Visual merchandising is an extremely important element as the first visual cue that affects buying behavior of customers. This study aims to identify determinants of visual merchandising that influence customers’ impulse buying behavior. This study focuses on five elements of visual merchandising which are window display, mannequin display, floor merchandising, promotional signage and lighting. Investigation was conducted at a popular fashion specialty store in Kuala Lumpur, Malaysia. A total of 150 customers' feedback was collected. Results of statistical data analysis show that three out of five visual merchandising elements are important in influencing the customers’ impulse buying behavior. Window display, mannequin display and promotional signage are positively related and identified as determinants of effective visual merchandising for impulse buying decision at the women fashion specialty store. The research outcome extends understanding on the adverse effect of visual merchandising on customers’ behavior.